Problems In Law of Mortgage Right Law Number 4 Tahun 1997 - et al., Muh Husein Ahmadi (International Journal of Advanced Science and Technology, 2019)
Mortgage Law disregarding a number of civil problems, the rights of the parties in the relationship of mortgage rights cannot be fulfilled equitably, because procedural practices so far have not proceeded properly. Law Number 4 of 1997 does not provide clear rules, therefore creditor tends to dominate in the legal relationship. At the same time, debtor rights are neglected, they do not get justice because of the creditors' negligence. This research is explanatory, laying the footing of knowledge about mortgage rights to be a foothold in further research. This study found non-normative offenses that must be included in the Mortgage Law for legal development and fulfillment of rights in the institutional security rights.